Current Trends in Upper and Lower Eyelid Blepharoplasty Among American Society of Ophthalmic Plastic and Reconstructive Surgery Members. Issue 1 (January 2018) - Kossler, Andrea L.; Peng, Grace L.; Yoo, Donald B.; Azizzadeh, Babak; Massry, Guy G.
Abstract : Purpose: To assess current practice patterns for management of upper and lower eyelid blepharoplasty by active American Society of Ophthalmic Plastic and Reconstructive Surgery members. Methods: An invitation to participate in a web-based anonymous survey was sent to the active American Society of Ophthalmic Plastic and Reconstructive Surgery membership via email. The survey consists of 34 questions, both multiple choice and free response, regarding upper and lower eyelid blepharoplasty surgery. Practice patterns for both aesthetic and functional blepharoplasty are assessed. Results: Thirty-four percent (161/472) of American Society of Ophthalmic Plastic and Reconstructive Surgery members polled responded to the survey. Members perform an average of 196 upper eyelid, 46 lower eyelid, and 53 four-eyelid blepharoplasty procedures per year, with 70% of cases being functional and 30% purely aesthetic. Most members prefer monitored care (71%) to local (21%) or general (8%) anesthesia. Eighty-nine percent of surgeons use topical antibiotics after surgery, erythromycin being the most common (51%). Fourteen percent of members use postoperative oral antibiotics, with cephalexin (81%) being most common. In upper eyelid blepharoplasty, orbicularis muscle is excised by 86% of respondents. Orbital fat is excised, when deemed appropriate, in 97% of cases, with nasal fat excised most commonly (88%). Less commonly, fat repositioning (36%) and adjunctive fat grafting (33%) are performed. In lower eyelid blepharoplasty, surgeons report using one or more of the following approaches: transconjunctival (96%), transcutaneous (82%), and both transconjunctival and transcutaneous (51%). Common adjunctive procedures include orbital fat excision (99%), fat repositioning (80%), and lateral canthal suspension (96%). Less common adjunctive procedures include laser skin resurfacing (36%) and chemical peels (29%). Conclusions: This report outlines contemporary practice patterns among active American Society of Ophthalmic Plastic and Reconstructive Surgery members in the management of upper and lower eyelid blepharoplasty. It is important to quantify such data periodically to update the membership as to how this common surgical procedure is approached. This also allows eyelid surgeons to compare their practice patterns with a national group specializing in such surgery. Abstract : Identifying contemporary surgical practice patterns among ASOPRS members in upper and lower blepharoplasty allows an update of how the society approaches this common oculofacial plastic procedure.Supplemental Digital Content is available in the text.